1991
DOI: 10.1007/bf00233846
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic intramuscular temperature fluctuations in the human forearm during cold-water immersion

Abstract: The purpose of the present study was to investigate the intramuscular temperature fluctuations in the human forearm immersed in water at 15 degrees C. Tissue temperature (Tt) was continuously monitored by a calibrated multicouple probe during 3 h immersion of the forearm. The probe was implanted approximately 90 mm distal from the olecranon process along the ulnar ridge. Tt was measured every 5 mm, from the longitudinal axis of the forearm (determined from computed tomography scanning) to the skin surface. Alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Other investigators have indirectly controlled for skin-fold differences between subjects but did not individualize temperature probe insertiondepth based on these measurements (4,5,17). These observations may help to explain the differences seen between past investigations and the current study.…”
Section: Discussionmentioning
confidence: 79%
“…Other investigators have indirectly controlled for skin-fold differences between subjects but did not individualize temperature probe insertiondepth based on these measurements (4,5,17). These observations may help to explain the differences seen between past investigations and the current study.…”
Section: Discussionmentioning
confidence: 79%
“…Ducharme et al (1991) measured intramuscular temperature gradients of the forearm during their prolonged cooling protocol, and reported that the fluctuations in temperature at the longitudinal axis of the forearm were not reflected in skin temperature. Therefore, it remains possible that the surface measurement we used to estimate FDI temperature did not accurately reflect FDI muscle temperature.…”
Section: Discussionmentioning
confidence: 98%
“…This cold-induced vasodilatation (CIVD) or 'hunting response' (Lewis 1930) is typically reported in extremities such as the finger (Keatinge 1957;Lewis 1930), hand (Chen et al 1996;Daanen et al 1997), feet (Fox and Wyatt 1962;Greenfield et al 1951), and ears and cheeks (Fox and Wyatt 1962), though more proximal body parts have also been reported to demonstrate CIVD. Fox and Wyatt (1962) found increases in skin temperature during cooling of the forearm and calf, and Ducharme et al (1991) also showed cyclic intramuscular temperature fluctuation during forearm cooling. During CIVD, blood flow has shown oscillatory changes similar to finger skin temperature, with blood flow changes preceding skin temperature changes by about 2 min (Daanen and Ducharme 1999).…”
Section: Introductionmentioning
confidence: 92%
“…It is likely that CIVD also improves the manual dexterity and tactile sensitivity during work in the cold. Since the blood flow increases substantially in the fingers during CIVD, this increases the blood circulation in the large vessels of the forearm, with the consequence of increasing the temperature of the forearm muscles (Ducharme et al 1991), and likely contributes to improved manual performance by improving muscle function. The increased skin temperature due to CIVD will increase the firing rate of the pressure transducers in the skin and thus increase tactile sensitivity.…”
Section: Introductionmentioning
confidence: 99%